THE FIVE FACTOR MODEL OF PERSONALITY AND INDIVIDUALISM / COLLECTIVISM IN SOUTH AFRICA: AN EXPLORATORY STUDY - Vogt, Liesl; Laher, Sumaya (PINS-Psychology in Society, 2025)
The Five-Factor Model (FFM) of personality is one of the prominent models in contemporary psychology and defines personality in terms of five broad factors, namely, Neuroticism, Extraversion, Openness to Experience, Agreeableness, and Conscientiousness. Recent research, however, questions the comprehensiveness of the FFM with evidence indicating the presence of other factors not addressed in the FFM most notably Individualism/Collectivism. Therefore, this study investigated the relationship of the FFM of personality to Individualism/Collectivism in a sample of 176 students from the University of the Witwatersrand using the Basic Traits Inventory and the Individualism/Collectivism scale. Results indicate that there were no significant relationships between the five factors and Individualism/Collectivism. In addition no significant difference was found between race and the five factors and Individualism/Collectivism. There were also no significant differences between home language and the five factors and Individualism/Collectivism.